National survey of knowledge, attitudes and perceptions about renewables and energy efficiency - Šegon, Velimir (Array, 2003)
A survey of knowledge, attitudes and perceptions about renewable energy sources (RES) and energy efficiency is currently being conducted for Croatia. The results presented in this article represent the first part of the survey, conducted in the city of Rijeka, for which a random sample of 600 people, age 18 or older, was selected out of a population of 150, 000. The analysis of the survey results indicates poor awareness of the benefits of biomass and bioenergy, leading to the conclusion that there is a strong need for starting educational programmes.